Sharjah biennial 16 To Carry: Guidebook (Sharjah Art Foundation, 2025)
Exhibition guidebook. Curators: Alia Swastika, Amal Khalaf, Megan Tamati-Quennell, Natasha Ginwala and Zeynep Oz. This publication is part of the Singing Wells' Sonic Inheritances, a project commissioned by Sharjah Art Foundation and Bergen Assembly , presented first at SB16, followed by the fifth edition of Bergen Assembly 2025, convened by Bergen School of Architecture (BAS), Adania Shibli and Ravi Agarwal.
English
Keywords: Biennial guidebook; N4390-5098 Visual Arts- Exhibitions; UAE -- Sharjah